Organoids to Study Intestinal Nutrient Transport, Drug Uptake and Metabolism – Update to the Human Model and Expansion of Applications - Zietek, Tamara; Giesbertz, Pieter; Ewers, Maren; Reichart, Florian; Weinmüller, Michael; Urbauer, Elisabeth; Haller, Dirk; Demir, Ihsan Ekin; Ceyhan, Güralp O.; Kessler, Horst; Rath, Eva (Frontiers in Bioengineering and Biotechnology, 2020)
Intestinal transport and sensing processes and their interconnection to metabolism are relevant to pathologies such as malabsorption syndromes, inflammatory diseases, obesity and type 2 diabetes. Constituting a highly selective barrier, intestinal epithelial cells absorb, metabolize, and release nutrients into the circulation, hence serving as gatekeeper of nutrient availability and metabolic health for the whole organism. Next to nutrient transport and sensing functions, intestinal transporters including peptide transporter 1 (PEPT1) are involved in the absorption of drugs and prodrugs, including certain inhibitors of angiotensin‐converting enzyme, protease inhibitors, antivirals, and peptidomimetics like β‐lactam antibiotics. Here, we verify the applicability of 3D organoids for in vitro investigation of intestinal biochemical processes related to transport and metabolism of nutrients and drugs. Establishing a variety of methodologies including illustration of transporter-mediated nutrient and drug uptake and metabolomics approaches, we highlight intestinal organoids as robust and reliable tool in this field of research. Currently used in vitro models to study intestinal nutrient absorption, drug transport and enterocyte metabolism, such as Caco2 cells or rodent explant models are of limited value due to their cancer and non-human origin, respectively. Particularly species differences result in poorly correlative data and findings obtained in these models cannot be extrapolated reliably to humans, as indicated by high failure rates in drug development pipelines. In contrast, human intestinal organoids represent a superior model of the intestinal epithelium and might help to implement the 3Rs (Reduction, Refinement and Replacement) principle in basic science as well as the preclinical and regulatory setup.